INTERPRETATION AND SOLUTION OF THE LIGHT CURVE OF THE WOLF-RAYET ECLIPSING BINARY CQ CEP - Kartasheva, T. A.; Svechnikov, M. A. (Одеські астрономічні публікації, 2017)
In spite of authors of numerous solutions of light curve of CQ Cep, which consider the latter as caused basically by effects of ellipsoidal form and components eclipse, we continue to insist upon the compound character of light curve of this very close system. We consider that about a half of amplitude of overwhelming majority of light curves of CQ Cep is caused by light variability of common system envelope which is utmost inhomogeneous is density and only a half is connected with the effects of ellipsoidal form and component eclipse. As a result of light curve correction for orbital eccentricity and introduction into consideration of a third brightness (the brightness of common envelope) a more precise solution has been obtained for light curve with the most low amplitude and, probably, less distorted by envelope inhomogeneities. The analysis of this solution allowed us to make more precise determination of the companion luminosity class, and to understand the reason of difficult detection of lines of the latter in the system spectrum, to make more precise the model of CQ Cep and its evolution in time, to understand the nature of high amplitude light curve of the system.